Tudor government - Morris, T. A. (Terence Alan), 1949- (Questions and analysis in history., 1999)
"Tudor Government surveys government across all the Tudor reigns, including those of Henry VIII, Mary and Elizabeth. It examines law and order, the government of the church and the personal role of the monarch. Combining narrative, questions and analysis, this book provides students with a clear background and a guide to examination success."--Jacket